2018
DOI: 10.1371/journal.pone.0191692
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal immunization with PspA (Pneumococcal surface protein A)-adsorbed nanoparticles targeting the lungs for protection against pneumococcal infection

Abstract: Burden of pneumonia caused by Streptococcus pneumoniae remains high despite the availability of conjugate vaccines. Mucosal immunization targeting the lungs is an attractive alternative for the induction of local immune responses to improve protection against pneumonia. Our group had previously described the development of poly(glycerol adipate-co-ω-pentadecalactone) (PGA-co-PDL) polymeric nanoparticles (NPs) adsorbed with Pneumococcal surface protein A from clade 4 (PspA4Pro) within L-leucine microcarriers (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…However, no binding to bacteria expressing PspA from clades 1 and 2 of family 1 was detected. In addition, immunizing the mucus membrane with NP/NCMP PspA4Pro was capable of inducing local and systemic antibodies that conferred partial protection against pneumococcus family 2 alone [146].…”
Section: Development Of Pneumococcal Nanovaccinesmentioning
confidence: 99%
“…However, no binding to bacteria expressing PspA from clades 1 and 2 of family 1 was detected. In addition, immunizing the mucus membrane with NP/NCMP PspA4Pro was capable of inducing local and systemic antibodies that conferred partial protection against pneumococcus family 2 alone [146].…”
Section: Development Of Pneumococcal Nanovaccinesmentioning
confidence: 99%
“…Furthermore, they successfully developed a NPMPs loaded with pneumococcal surface protein A (PspA) as DPI vaccine against pneumococcal infection that successfully induced antibody response against in vitro DCs line [50]. Recently, this work was continued by Rodrigues et al, which demonstrated successful vaccination antibody production through in vivo study via lung instillation in mice compared to subcutaneous injection [51]. …”
Section: Aerosolized Delivery Strategies For Macromolecule Drug Deliverymentioning
confidence: 99%
“…To replace a mix of 13 to 20 serotypes of pneumococcus, Butantan developed a vaccine based on recombinant pneumococcal surface protein A (PspA) from three different strains, making production easier and less expensive [40][41][42].…”
Section: Pneumococcal Vaccinementioning
confidence: 99%